Efecto de los métodos de siembra a chorro continuo y trasplante, con diferentes densidades de siembra sobre parámetros de crecimiento y rendimiento en el cultivo de quinua (Chenopodium quinoa Willd.) bajo condiciones controladas, en el sector La Argelia, Loja - Castro Calderón, Silvana Estefani (2024)
Quinoa is an Andean crop considered important for its nutritional and agronomic value, as well as for its ability to adapt to climate change and diverse environments. In recent years quinoa has been in great demand in the international market, promoting its cultivation in new production areas. In Ecuador, the producing provinces of this crop are Chimborazo, Cotopaxi, Imbabura, Pichincha, Carchi, Tungurahua, which in 2021 generated a national yield of 0,62 t ha-1 and by 2022 with 1,34 t ha-1 . Agronomic practices such as proper management of planting systems and good plant distribution will increase yields. In this context, the present study aimed to evaluate the effect of continuous jet seeding and transplanting methods with different planting densities on growth and yield parameters in the quinoa crop, under controlled conditions, in La Argelia area of Loja canton. For this purpose, a completely randomized design (CRD) was used, with a bifactorial arrangement with 6 treatments and three replications. The densities were 20, 13 and 8 plants m-2 . The following variables were evaluated: phenology, temperature, relative humidity, plant height, stem diameter, leaf area index, biomass at the beginning of flowering m-2 , main panicle length, main panicle weight, harvest biomass m-2 , number of grains plant-1 , number of grains m-2 , weight 1000 grains, yield and harvest index. With respect to the treatments evaluated, significant effects were found in the variable stem diameter, with the transplanting treatment * 8 plants m-2 (T6), presenting the best average of 1,37 cm and the smallest diameter with the transplanting treatment * 20 plants m-2 (T4), with 0,94 cm. As for the sowing method factor, it showed effects on the variables height, leaf area index, being greater in direct sowing to continuous jet, in addition, the sowing methods affected phenology, causing a delay of 7 days more to reach physiological maturity in the transplant sowing method, with respect to continuous jet. Thus, it was observed that the leaf area index, biomass at the beginning flowering m-2 , biomass at harvest m-2 , number of grains m-2 and yield t ha-1 had better responses to the increase in density with 20 plants m-2 , while the stem diameter, length and weight of the main panicle and number of grains plant-1 showed the best results with the low density of 8 plants m-2 . These responses were obtained as a result of the analysis of individual plants, indicating that as the number of plants decreases, increasing values are presented, probably due to the decrease in competition for available resources among plants.